Mini-piezometers for Measuring Groundwater to Surface Water Exchange - Christopher J. Martinez (EDIS, 2010)
AE454, a 6-page illustrated fact sheet by Christopher J. Martinez, aids those who are engaged in surface water to groundwater exchange studies in cost-effective construction, installation and use of mini-piezometers. Includes references. Published by the UF Department of Agricultural and Biological Engineering, December 2009.